Diagnostic yield of chromosomal microarray and trio whole exome sequencing in cryptogenic cerebral palsy. Issue 8 (28th July 2021) - Yechieli, Michal; Gulsuner, Suleyman; Ben-Pazi, Hilla; Fattal, Aviva; Aran, Adi; Kuzminsky, Alla; Sagi, Liora; Guttman, Dafna; Schneebaum Sender, Nira; Gross-Tsur, Varda; Klopstock, Tehila; Walsh, Tom; et al.
Abstract : Objective: To determine the yield of genetic diagnoses using chromosomal microarray (CMA) and trio whole exome sequencing (WES), separately and combined, among patients with cryptogenic cerebral palsy (CP). Methods: Trio WES of patients with prior CMA analysis for cryptogenic CP, defined as disabling, non-progressive motor symptoms beginning before the age of 3 years without known cause. Results: Given both CMA analysis and trio WES, clinically significant genetic findings were identified for 58% of patients (26 of 45). Diagnoses were eight large CNVs detected by CMA and 18 point mutations detected by trio WES. None had more than one severe mutation. Approximately half of events (14 of 26) were de novo. Yield was significantly higher in patients with CP with comorbidities (69%, 22 of 32) than in those with pure motor CP (31%, 4 of 13; p=0.02). Among patients with genetic diagnoses, CNVs were more frequent than point mutations among patients with congenital anomalies (OR 7.8, 95% CI 1.2 to 52.4) or major dysmorphic features (OR 10.5, 95% CI 1.4 to 73.7). Clinically significant mutations were identified in 18 different genes: 14 with known involvement in CP-related disorders and 4 responsible for other neurodevelopmental conditions. Three possible new candidate genes for CP were ARGEF10, RTF1 and TAOK3 . Conclusions: Cryptogenic CP is genetically highly heterogeneous. Genomic analysis has a high yield and is warranted in all these patients. Trio WES has higher yield than CMA, except in patients with congenital anomalies or major dysmorphic features, but these methods are complementary. Patients with negative results with one approach should also be tested by the other.